Evaluation Of Development Of Futsal Sports Achievement Of Futsal Kawat Duri Fc On Malang City - Ahmad Rizqi Syaifuddin; Fiqi Isnandar; Nursyafiqri Ilmiardi; Thoyib Prayogo; Yoga Teja Kartika; Prisca Widiawati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Futsal is a sport that is currently favored with various layers of society around the world, because this game is quite simple and is able to attract attention and feelings and presents deep drama and extraordinary techniques throughout the game. The purpose of this research is to identify coaching, training programs, organization, and infrastructure facilities as the main aspects of the implementation of achievement development at Kawat Duri Fc in Malang City. The approach used in this study is a qualitative descriptive approach, namely information in the form of observations, documentation and interviews on the management of the futsal club at the Kawat Duri Futsal Team Malang by sharing explanations about the facts as they are and without concealment. In the research on futsal coaching at Kawat Thorn FC, it can be interpreted that the coaching carried out by the Futsal Kawat Duri to athletes and fellow management is good and communicative. The Futsal Barbed Wire training program is less detailed because it is not explained in writing and the program to becarried out is clearly defined. The management organization at the Malang, Kawat Duri Futsal Club is listed in good and organized criteria. The facilities and infrastructure owned by Kawat Duri Futsal are adequate and have relatively good conditions.